BetaFIT: A computer program to fit pointwise potentials to selected analytic functions. (January 2017) - Le Roy, Robert J.; Pashov, Asen
Abstract: This paper describes programbetaFIT, which performs least-squares fits of sets of one-dimensional (or radial) potential function values to four different types of sophisticated analytic potential energy functional forms. These families of potential energy functions are: the Expanded Morse Oscillator (EMO) potential [J Mol Spectrosc 1999;194:197], the Morse/Long-Range (MLR) potential [Mol Phys 2007;105:663], the Double Exponential/Long-Range (DELR) potential [J Chem Phys 2003;119:7398], and the "Generalized Potential Energy Function (GPEF)" form introduced by Šurkus et al. [Chem Phys Lett 1984;105:291], which includes a wide variety of polynomial potentials, such as the Dunham [Phys Rev 1932;41:713], Simons–Parr–Finlan [J Chem Phys 1973;59:3229], and Ogilvie–Tipping [Proc R Soc A 1991;378:287] polynomials, as special cases. This code will be useful for providing the realistic sets of potential function shape parameters that are required to initiate direct fits of selected analytic potential functions to experimental data, and for providing better analytical representations of sets of ab initio results. Abstract : Highlights: Computer program for fitting a pointwise diatomic molecule potential energy function to four types of sophisticated analytic functions. Essential for providing trial parameters for direct fits of experimental data to potential functions with one of these forms. Useful for converting (pointwise) ab initio potentials into a portable, useful form.